Neoamphimedine Circumvents Metnase-Enhanced DNA Topoisomerase IIα Activity Through ATP-Competitive Inhibition - Ponder, Jessica (Molecular Diversity Preservation International, 2011)
Type IIα DNA topoisomerase (TopoIIα) is among the most important clinical drug targets for the treatment of cancer. Recently, the DNA repair protein Metnase was shown to enhance TopoIIα activity and increase resistance to TopoIIα poisons. Using in vitro DNA decatenation assays we show that neoamphimedine potently inhibits TopoIIα-dependent DNA decatenation in the presence of Metnase. Cell proliferation assays demonstrate that neoamphimedine can inhibit Metnase-enhanced cell growth with an IC(50) of 0.5 μM. Additionally, we find that the apparent K(m) of TopoIIα for ATP increases linearly with higher concentrations of neoamphimedine, indicating ATP-competitive inhibition, which is substantiated by molecular modeling. These findings support the continued development of neoamphimedine as an anticancer agent, particularly in solid tumors that over-express Metnase.